POTENSI DAYA TARIK DAN PERSEPSI PENGUNJUNG TERHADAP EKOWISATA LAUT DI PULAU HARAPAN, TAMAN NASIONAL LAUT KEPULAUAN SERIBU (TNKpS) - Meyliana Astriyantika; Harnios Arief; Tutut Sunarminto (Department of Forest Resources Conservation and Ecotourism - IPB University, 2015)
Harapan Island is the area of the island situated in the settlement of the KepulauanSeribu Marine National Park (TNKpS). The abundance of natural resources of the sea and the beauty of the natural landscape into a tourist attraction to this location, so it looks the existence value of benefits and high economic value. This study done to assess the potential of natural resources to be the object of ecotourism activities in the Harapan island KepulauanSeribu Marine National Park (TNKpS), as well as assess the perceptions of visitors who do the activities of ecotourism in the location to know how the assessment of visitors to the satisfaction felt.Research conducted in december 2014 until april 2015, using a questionnaire, interviews and observations roomy to look at the location and the availability of the object of attraction.The results that the visitors who come to the location of the Harapan island in the dominant is the visitors who come in groups, and visitors can feel satisfied with what they get from ecotourism activities in the Harapan island. Harapan island of being the places are in the zone TNKpS settlement with the potential of natural resources abiotik (23,43%), algae (19,66%), hard corals (50,07%), soft corals (0,00%), corals die (3,24%), and biota other (3,60%).But as the object to the main tourist activities in the island of hope that is the beauty of the sea, coral reefs, ornamental fish and as tourist attraction of maritime and coastal tourist attractive to visitors.Based on the results of research, the latest data in TNKpS known that there are 36 the type of coral reefs and 56 kind of ornamental fish in the Harapan island. Keyword: harapan Island, Kepulauan Seribu National Park, marine ecotourism, perception of visitors, the potential of attractiveness